2017
DOI: 10.12973/ejmste/78243
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Demands in Mathematics and Mathematical Literacy: A Case of Mathematics and Mathematical Literacy Teachers and Facilitators

Abstract: The purpose of this article is to examine teachers' and facilitators' (subject advisors) views of the approaches to teaching mathematics and mathematical literacy (ML). Using Bernstein's (1996) constructs of recognition and realisation rules, I analysed data from interviews conducted with mathematics and ML teachers and facilitators. The analysis shows that some teaching strategies are associated with mathematics and others with ML. That is, teachers and facilitators refer to teaching strategies that are doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 14 publications
1
33
0
12
Order By: Relevance
“…As evidenced by persistence and positive emotions, the students were more engaged if they could see the relevance of math and felt they were better able to discuss mathrelated topics with their peers. Motivation to learn math is a global concern, and ML has been the subject of much attention in the past decade (Machaba, 2018;Masal & Yılmazer, 2014;Uzunboylu et al, 2012;Vithal & Bishop, 2006), particularly in how to engage students and integrate ML into math lessons (Machaba, 2018;Vithal & Bishop, 2006). In the present study, the major finding is that ML significantly affected students' engagement, and the students also confirmed that they learned math content and, in particular, how math relates to everyday life.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As evidenced by persistence and positive emotions, the students were more engaged if they could see the relevance of math and felt they were better able to discuss mathrelated topics with their peers. Motivation to learn math is a global concern, and ML has been the subject of much attention in the past decade (Machaba, 2018;Masal & Yılmazer, 2014;Uzunboylu et al, 2012;Vithal & Bishop, 2006), particularly in how to engage students and integrate ML into math lessons (Machaba, 2018;Vithal & Bishop, 2006). In the present study, the major finding is that ML significantly affected students' engagement, and the students also confirmed that they learned math content and, in particular, how math relates to everyday life.…”
Section: Discussionsupporting
confidence: 58%
“…In the current study, the aim was for students to learn math concepts and math literacy (ML), which has emerged as an important concept in math education (e.g., Machaba, 2018;Masal & Yılmazer, 2014;Uzunboylu, Arslan, & Yavuz, 2012;Vithal & Bishop, 2006). ML offers new ways of enhancing students' motivation to learn math, making it more meaningful in real-life contexts and better able to tackle emotional issues, such as math anxiety.…”
Section: Learner-driven Knowledge Creation and Math Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Asimismo, sin este tipo de comprensión no se puede acceder a los conocimientos básicos de matemáticas para actuar en un contexto cotidiano, es decir, alcanzar la alfabetización matemática o "mathematical literacy" (Machaba, 2018).…”
Section: Gradounclassified
“…The learners do not draw pictures or diagrams as solution strategies to help them with mathematical problems. (Machaba, 2018). From our experiences, we noted that Grade 12 learners tend to leave out the sections on coordinate and transformation geometry during the examination at the end of the year or perform poorly in these sections (Limpopo Department of Education (LDoE), 2009).…”
Section: Introductionmentioning
confidence: 99%